Teaching the Ba-construction with Augmented Reality in Online Learning Environments - Wang, Lu (δ, 2021)
The ba-construction is a unique but frequently used grammatical construction in the Chinese language. Understanding and using the ba-construction precisely and appropriately are the major hurdle of the grammatical difficulties to Chinese Foreign Language (CFL) learners. In face-to-face learning contexts, CFL teachers are inclined to use the Total Physical Response (TPR) method to help students understand the “disposing” nature of the ba-construction. Given pandemic lockdowns and the development of educational technology, formal CFL instructions have partly integrated online components or shifted toward online learning contexts. Challenges are provoked when traditional Chinese grammar instructions are constrained by geographic locations and limited resources. This study seeks to address the gap in the literature by examining whether Augmented Reality (AR) technology can facilitate online instructions of the Chinese ba-construction through its unique affordance. Furthermore, the study seeks to determine if CFL learners are more engaged in the AR-aided online instructions than others without the AR treatment. In this study, a between-groups quasi-experiment was designed involving 12 adult CFL learners. The experiment was administered in three instruction sessions for two weeks. Same grammatical assessments and engagement surveys were assigned to the AR group and the non-AR group after each instruction. The results indicated a statistically significant difference in favour of the AR group related to learners’ explicit grammatical knowledge and pragmatic knowledge. The use of AR has enhanced participants’ cognitive engagement. Although preliminary, this study can shed light on the design of AR-aided communicative instruction for CFL educators and AR-assisted language learning researchers.
Keywords: ba-construction